Complexity and rationality: a material-systemic approach. Issue 2 (14th September 2018) - Andersen, Lars
Abstract : Purpose: The purpose of this paper is to contribute to solving the complexity problem as increased complexity is a main reason why projects fail to reach their goals, and it is unclear what complexity is. Design/methodology/approach: Conceptual development integrating theories of materiality, teleology, and complexity, decision-making theory, communication theory, coordination theory, and qualitative, quantitative and participatory approaches are used in this paper. Findings: To understand complexity, it is necessary to develop a material-systemic process approach and to distinguish structured from unstructured complexity. The social actors construct a complex material-systemic process between themselves and nature to handle unwieldy outer nature. The material-systemic approach reveals how materiel life-world arenas are developed through increased complexity and specialization. Handling complexity is possible by materiality in general and structural material in special, the interplay between inner time (planning) and outer time (production), and between human subjects and an underlying coordination mechanism. It is a systematic organizational blockade that reproduces internal complexity as unstructured and incomprehensible complexity. Research limitations/implications: The practical models of organizing are tested to the highest degree in construction industry. It is a task to try and examine the models in other types of projects. Originality/value: The paper offers a proposal to a theoretical solution to the complexity problem going back to the roots in Enlightenment and shows at the same time through practical models how increased complexity may be the most important productive force in future projects.